Incienso Macho del Cuzco o Benjuí del Perú - Maldonado, Angel (1919)
In the market and grocery staples, from Cuzco, a resinous substance is sold under the name of Incense Macho, which is used as incense in religious ceremonies or odorized room environment; It also alcoholo dissolved in wine is used as a mouthwash for conditions of the gums; and in the manufacture of various patches and plasters used in folk medicine. Their origin is a state of the mountain valleys of Cuzco and others, in the valleys of the region of Beni in Bolivia. As for the botanical origin nothing is known for sure, and even some traders say is a resinous substance composed of several others of similar nature, without specifying which ones.